Energy Operations for Resident and Its Implications for Economic Growth: Indonesia’s New Capital City as a Case Study - Rosyadi, Rosyadi; Hasid, Zamruddin; Purwadi, Purwadi (International Journal of Energy Economics and Policy, 2023)
The topic of "IKN" is not just a discourse. This is good news for Indonesia which is trying to be free from prosperity conflicts, which so far have only been concentrated in one area. What is more crucial is that the struggle for economic resources is also always won by regions that have inclusive GRDP growth, competitive workers, and solid infrastructure facilities, especially in Java. This is because regions such as Kalimantan, their economic prospects are sinking because the transformation of consumption and purchasing power is not working. Therefore, this paper initiates the relationship between population, electricity, water production, and regional/GRDP growth in the center of IKN and 4 buffer zones. Systematics in data extraction uses panel regression which presents time-series data (8 periods). Valuable insights conclude some important findings. The population has been proven to increase electricity in PPU, Paser, Balikpapan and Samarinda. Positive causality also indicates the effect of population on water production in PPU and Balikpapan. However, it also influences positively. On the other hand, electric power has a positive impact on economic growth in PPU, while in Paser, water production actually increases economic growth. Population as the only variable that has no effect on economic growth in all cases. Only Kukar has all the opposite variables and has a negative effect. Finally, preparations towards a fair IKN development perspective consider long and short term policy packages.